Kandungan Gizi dan Organoleptik Biskuit dengan Subtitusi Tepung Sukun dan Stevia - Muhlishoh, Arwin; Aryanti Setyaningsih; Zuhria Ismawanti (UNIVERSITAS NGUDI WALUYO, 2021)
Breadfruit flour is a local food ingredient that can be used as a substitute for flour with a low glycemic index content, as well as high levels of starch, amylose and resistant starch. While stevia is a source of natural sweeteners with a sweetness level of 200-300 times sweeter than cane sugar. Both ingredients are safe for patients with diabetes mellitus. This study was conducted to evaluate the nutritional and organoleptic content of biscuits substituted with breadfruit and stevia flour. Nutritional content was carried out by proximate test. Meanwhile, the organeleptic test was carried out by the hedonic test. The study was conducted using a completely randomized design with four proportion factors adding 15-50% breadfruit flour, while 8 grams of stevia was added. There was a significant difference in the average organoleptic test for each treatment of breadfruit flour and stevia biscuit formulations (p<0.05). From the results of the different test using Tukey HSD, it is known that the respondents